In Vitro Bioavailability Study of an Antiviral Compound Enisamium Iodide - Eleonore Haltner-Ukomadu; Svitlana Gureyeva; Oleksii Burmaka; Andriy Goy; Lutz Mueller; Grygorii Kostyuk; Victor Margitich (MDPI AG, 2018)
An investigation into the biopharmaceutics classification and a study of the in vitro bioavailability (permeability and solubility) of the antiviral compound enisamium iodide (4-(benzylcarbamoyl)-1-methylpyridinium iodide) were carried out. The solubility of enisamium iodide was determined in four different buffers. Apparent intestinal permeability (Papp) of enisamium iodide was assessed using human colon carcinoma (Caco-2) cells at three concentrations. The solubility of enisamium iodide in four buffer solutions from pH 1.2 to 7.5 is about 60 mg/mL at 25 °C, and ranges from 130 to 150 mg/mL at 37 °C, depending on the pH. Based on these results, enisamium iodide can be classified as highly soluble. Enisamium iodide demonstrated low permeability in Caco-2 experiments in all tested concentrations of 10-100 μM with permeability coefficients between 0.2 × 10−6 cm s−1 and 0.3 × 10−6 cm s−1. These results indicate that enisamium iodide belongs to class III of the Biopharmaceutics Classification System (BCS) due to its high solubility and low permeability. The bioavailability of enisamium iodide needs to be confirmed in animal and human studies.